Implementation of Legal Protection of Confidential obligation Notary In Running Position - Djuniatno Hasan; Agus Ekhsan; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
This research aims to: 1)To know and understand, that notaries who runs the office for public use, in addition to protection by the State, as well as the protection of Indonesian Notary Association and Honorary Council of Notaries; 2) Assess and analyze about a Notary that in using the rights and obligations dissenter contained in the Law on Notary, and legislation more specifically and expressly provides that the Notary concerned shall provide information, and in this case when the Notary the unlock the secrets of (the contents of) the deed; 3)To assess, and to know what are the weaknesses, as well as a solution to the problems in the implementation of legal protection in carrying secret notary office as a notary public.Type of this research is by using a normative juridical approach of the Act (statute approach), Conceptual approach. Legal materials used are the primary law materials, secondary law, and the tertiary law.Based of this study concluded that: 1) Under the provisions of Act No. 2 of 2014, amendments to the Act No. 30 of 2004 Article 4 and Article 16 paragraph (1) letter f, that Notaries have the authority and obligation to keep professional secrecy regarding the Deed and any information obtained in the manufacture of deed and conceal the contents of the deed and he knew a good description of the past, present and future; 2) that the Notary is obliged and has a right of refusal on the confidentiality deed that has been made and all information obtained for a deed in accordance with the oath / pledge of office, unless the law determines the other; and 3) Based on the description of the foregoing in the implementation of the legal protection of notary there are still weaknesses in terms of both implementation and legal certainty. Hope writer immediately formed a legislation or regulation, regulate the enforcement of justice, as well as agencies or other legal institutions.Keywords: Notary; Rights and Obligations of Ingratitude Secrets Office.